Enhancing mechanical properties and dimensional stability of phenolic resin-treated plybamboo - FARN, Fadhlia; MT, Paridah; UMK, Anwar; AH, Juliana; A, Zaidon (Forest Research Institute Malaysia, 2017)
This study evaluated the mechanical properties and dimensional stability of 3-ply phenolic-treated plybamboo influenced by treatment methods, namely, impregnation and soaking for 30, 60 and 90 min. Medium molecular weight phenol formaldehyde (MMwPF) resin with 1500 g mol-1 was applied to bamboo (Gigantochloa scortechinii) slivers of 2-mm thickness following resin treatments. The phenolic-treated bamboo slivers were precured at 60 °C for 6 hours, followed by hot pressing at 140 °C for 15 min to produce a 3-ply phenolic-treated plybamboo. Untreated boards were prepared using commercial phenol formaldehyde resin as binder. Use of MMwPF resin increased the density of boards. Modulus of rupture and impact resistance of the samples were significantly affected (p ≤ 0.01) by treatment methods but treatment duration did not show any significant effect. Reduced water absorption, thickness swelling and linear expansion suggested improved dimensional stability of the phenolic-treated sample. Treatment with phenolic resin markedly increased anti-shrinkage efficiency at p ≤ 0.05. Impregnation was more effective compared with soaking method.